2019
DOI: 10.1186/s12931-018-0968-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of blood inflammatory markers by benralizumab in patients with eosinophilic airway diseases

Abstract: BackgroundBenralizumab, a humanized, afucosylated, monoclonal antibody that targets interleukin-5 receptor α, depletes eosinophils and basophils by enhanced antibody-dependent cell-mediated cytotoxicity. It demonstrated efficacy for patients with moderate to severe asthma and, in a Phase IIa trial, for chronic obstructive pulmonary disease (COPD) with eosinophilic inflammation. We investigated effects of benralizumab 100 mg every 8 weeks (first three doses every 4 weeks) subcutaneous on blood inflammatory mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 65 publications
2
48
0
1
Order By: Relevance
“…Furthermore, both doses also led to significant upregulation of the gene coding for the anti-inflammatory interleukin 10 receptor (IL-10RB) [15] and of the suppressor of cytokine signalling 3 (SOCS3) [22], and significantly modulated genes toward a positive regulation of the vitamin D pathway [23][24][25][26][27] (upregulation of VDR, RXR, DHCR7) and toward a negative regulation of oxidative stress [23,28,29] (upregulation of SESN2, HP, CYGB and downregulation of ATG7, CD1B, NCF1), Th2 cytokine production [23,30] (upregulation of SCGB1A1 and TNFRSF21), B cells activation/proliferation [23,31] (upregulation of SAMSN1, INPP5D) and significant downregulation of the eosinophil major basic protein (PRG2) [32]. With both doses, genes associated with eosinophils and basophils were significantly downregulated (CLC, OLIG1, OLIG2 and PRSS33) [33]. Treatment with the highest dose also significantly downregulated genes coding for the pro-inflammatory and mucus producer mitogen-activated protein kinase 13 (MAPK13) [23,34], the cytotoxicity natural killer cell triggering receptor NCR3 [23], significantly upregulated the metalloproteinase inhibitor TIMP1 [23,35] and the neutrophil elastase inhibitor SER-PINB1 [36], and significantly modulated genes toward positive regulation of ciliary function (IFT88, DNAI2, DNAI1) [23,37,38].…”
Section: Inflammatory Gene Interaction Network Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both doses also led to significant upregulation of the gene coding for the anti-inflammatory interleukin 10 receptor (IL-10RB) [15] and of the suppressor of cytokine signalling 3 (SOCS3) [22], and significantly modulated genes toward a positive regulation of the vitamin D pathway [23][24][25][26][27] (upregulation of VDR, RXR, DHCR7) and toward a negative regulation of oxidative stress [23,28,29] (upregulation of SESN2, HP, CYGB and downregulation of ATG7, CD1B, NCF1), Th2 cytokine production [23,30] (upregulation of SCGB1A1 and TNFRSF21), B cells activation/proliferation [23,31] (upregulation of SAMSN1, INPP5D) and significant downregulation of the eosinophil major basic protein (PRG2) [32]. With both doses, genes associated with eosinophils and basophils were significantly downregulated (CLC, OLIG1, OLIG2 and PRSS33) [33]. Treatment with the highest dose also significantly downregulated genes coding for the pro-inflammatory and mucus producer mitogen-activated protein kinase 13 (MAPK13) [23,34], the cytotoxicity natural killer cell triggering receptor NCR3 [23], significantly upregulated the metalloproteinase inhibitor TIMP1 [23,35] and the neutrophil elastase inhibitor SER-PINB1 [36], and significantly modulated genes toward positive regulation of ciliary function (IFT88, DNAI2, DNAI1) [23,37,38].…”
Section: Inflammatory Gene Interaction Network Analysismentioning
confidence: 99%
“…In addition, differentially regulated genes, pathways, biological processes and molecular functions were considered significant only upon correction for multiplicity (pFDR< 0.05). Few previous studies have investigated gene expression by microarray in blood after treatment of COPD patients with anti-inflammatory agents [33,55,56] and most of them did not correct for multiplicity [55,56]. One study evaluated the effect of azithromycin by microarray both in blood and sputum of COPD patients, although the analyses were not corrected for placebo [57].…”
mentioning
confidence: 99%
“…Benralizumab, was tested in patients with eosinophilic COPD (ClinicalTrials.gov Identifier: NCT01227278) administered every 4 weeks (Q4W) (weeks 1, 4 and 8), and then Q8W (weeks 16, 24, 32, 40 and 48). It was observed that genes related to basophil or eosinophil, such as the serine protease PRSS33 were downregulated by benralizumab [143]. SB010, a GATA3-specific DNAzyme, was tested in COPD patients with sputum eosinophilia (DRKS00006087), in which patients inhaled SB010 for 28 days.…”
Section: Granulocyte-targeted Therapies For Copdmentioning
confidence: 99%
“…Current treatment guidelines for chronic inflammatory airway diseases all rely to a greater or lesser extent on antiinflammatory therapeutics, particularly corticosteroids, as well as infection control when necessary [10][11][12]. Next-generation monoclonal therapies have shown promise in COPD, asthma, CRS, and AR [13][14][15][16]. However, these therapies remain expensive and beyond the reach of developing countries where the majority of the world's population reside and where the prevalence of allergic respiratory disease is likely to rise alongside increasing urbanization [2,17].…”
Section: Unmet Needs In Chronic Inflammatory Airway Diseasesmentioning
confidence: 99%